PURWARUPA ROBOT PEMADAM API DENGAN SENSOR ULTRASONIC DAN ULTRAVIOLET BERBASIS AT89S52 - Wahyu Sapto Aji; Fajar Hermawanto; Muchlas Muchlas (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
The fire often takes many victims. Fire detection system sometime can not prevent this from happening. Therefore, it is essential to develop a robot that can detect the present of fire as well as extinguish it. This research aimed to design a fire extinguisher robot using AT89S52 microcontroller as its controller. A DC fan controlled by a relay is utilized to put out the fire and a fire sensor (UV-Tron) is used to detect the presence of fire. The movement of the robot is driven by motor DC. The robot can detect the surrounding obstacles and possess an ultrasound-based navigation system. If the ultrasound system detects an obstacle, the robot will automatically turn without colliding the obstacle or other things around it. The result has shown that this fire extinguisher robot can be built using hardware and software controlled by an AT89S52 microcontroller. It can be concluded from the tests that the robot can detect fire as far as 5 meter distance and able to successfully put out the fire.